Implementasi Program Tikasim (Tirta Kencana Siap Minum) di Lapas Kelas II B Kabupaten Jombang - Fransisca Fernandita; Nawangsari, Ertien Rining (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the implementation of the TIKASIM (Tirta Kencana Siap Minum) program in Class II B Correctional Institution Jombang Regency. Using the theory according to George C. Edwards III by looking at four indicators which include communication, resources, disposition, and bureaucratic structure. This research was compiled using a qualitative approach. Obtaining primary data sources from interviews and observations is complemented by secondary data such as images, journals, reports, previous research, and other archives that have relevance. The research locus is in Class II B Correctional Institution of Jombang Regency. The results of the study show that the communication indicators in the implementation of the TIKASIM Program have been running well, explained by the clear and consistent transmission of information between Perumdam Tirta Kencana Jombang and Class II B Jombang Correctional Facility. Then the resource indicator is also quite well supported by a sufficient number of staff and adequate facilities. The disposition or attitude of policy implementers also shows communication and commitment among the entire implementation team. The bureaucratic structure has been running according to the guidelines of PERMENKUMHAM number 40 of 2017 concerning Guidelines for the Implementation of food for Prisoners, children and Prisoners.